The intranational intelligibility of Hong Kong English accents. (April 2015) - Sewell, Andrew
Abstract: Intelligibility, usually defined as the ability of the listener to recognize words and utterances, is an important consideration for international communication in English. Most research studies have focused on international intelligibility, involving speakers from different language backgrounds. However, there have been few studies of intranational intelligibility, and little is known about how well speakers from 'the same' language background understand one another. This study investigated the relationship between accent features and intranational intelligibility by providing 91 listeners in Hong Kong with a range of speech samples taken from Hong Kong media broadcasts in English. These samples contained different combinations of accent features, reflecting different kinds of Hong Kong English accents. Listeners were required to produce orthographic transcripts of the speech samples. Transcript analysis produced a list of words that were frequently mistranscribed, and identification of the accent features involved showed that consonantal modifications were often associated with intelligibility problems. The findings suggest that certain L1-related accent features are capable of reducing intranational intelligibility, as are other accent features and speech processes used by both L1 and L2 English speakers. The study has implications for pronunciation pedagogy, and for those involved with intranational and international communication in English.